A guide to senolytic intervention in neurodegenerative disease. (December 2021) - Lee, Suckwon; Wang, Ellen Y.; Steinberg, Alexandra B.; Walton, Chaska C.; Chinta, Shankar J.; Andersen, Julie K.
Highlights: Evidence suggests that senescent cell killing by senolytic compounds may be a new intervention in neurodegeneration. Senolytics differ on their mechanism of action and different senolytics can kill different cell types. The heterogeneity of senolytics has been overlooked in neurodegeneration research and may explain existing controversies. The present review provides a guide to the use of senolytics in the brain to aid in future studies. Abstract: Cellular senescence is a potential tumor-suppressive mechanism that generally results in an irreversible cell cycle arrest. Senescent cells accumulate with age and actively secrete soluble factors, collectively termed the 'senescence-associated secretory phenotype' (SASP), which has both beneficial and detrimental effects. Although the contribution of senescent cells to age-related pathologies has been well-established outside the brain, emerging evidence indicates that brain cells also undergo cellular senescence and contribute to neuronal loss in the context of age-related neurodegenerative diseases. Contribution of senescent cells in the pathogenesis of neurological disorders has led to the possibility of eliminating senescence cells via pharmacological compounds called senolytics. Recently several senolytics have been demonstrated to elicit improved cognitive performance and healthspan in mouse models of neurodegeneration. However, their translation for use in the clinic still holds several potential challenges. This review summarizes available senolytics, their purported mode of action, and possible off-target effects. We also discuss possible alternative strategies that may help minimize potential side-effects associated with the senolytics approach.